Transition of care: Nurses' perception in an emergency service - Pedro Costa (2022)
Effective communication among healthcare professionals while sharing clinical information is crucial to ensure the safety of care. Adverse events occur as a result of communication failures. Goals: To understand nurses' perception of the handover in an emergency service, taking into account the continuity of health care. Methods: A qualitative, exploratory study, developed in a medical-surgical emergency department in the northern region of Portugal. Use of a non-probabilistic convenience sampling consisting of 14 nurses, including general and specialist nurses, with minimum experience of a year in the emergency service. Data were collected between April and June 2021 through a semi-structured interview. Data were analyzed through thematic content analysis, with mixed categorization. Data analysis has been done according to Bardin's assumptions and was aided by the MAXQDA 2020 Analytics Pro software. Results: Five categories were evidenced - "security of the transition of care", "continuity of health care", "valorization of autonomy", "formative role of the transition of care”, "confidentiality of information” – which integrate the theme "importance of the transition of health care". Conclusions: The main conclusions are: i) the transition of care in the emergency service is influenced by the patients’ influx; (ii) the information handed over is crucial in order to determine priorities and the continuity of care; iii) regarding the information to be transmitted, the biomedical model is still dominant; iv) the transition of care should assume a formative role within the nursing team; and v) the confidentiality of clinical information is a challenge to healthcare professionals.